PEMBELAJARAN DENGAN METODE FOLLOW THE LINE (FTL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN AL-QUR’AN HADITS KELAS 1 DI MADRASAH IBTIDAIYAH - Himmatul Husniyah; Nayla Fadiatus Silvia (STIT Muhammadiyah Paciran Lamongan, 2025)
This research discusses the influence of the Follow The Line (FTL) learning method on student learning outcomes in Al-Qur'an Hadith subjects Class I Madrasah Ibtidaiyah. Against the background of students who lack interest in learning to read and write the Al-Qur'an, there are still students who are less accustomed to reading and writing the Al-Qur'an and have different student backgrounds, as well as teachers who still use conventional learning or teachers who dominate the learning process, especially in Al-Qur'an Hadith subjects. To address this problem, researchers are interested in using the Follow The Line (FTL) Learning Method as the main model in the Al-Qur'an Hadith learning process. The formulation of the problem behind the research is